Contact Centre Agents’ Perception on Technology Adoption in Promoting Quality Customer Service - Modjela, Nathaniel; Mkhomazi, Sharol Sibongile (African Journal of Inter/Multidisciplinary Studies, 2025)
A contact centre is a central key to any organisation and a tool for managing customer service in any private and public organisation. Technology today plays a significant role in the contact centre environment. For the organisation to provide effective customer service, a contact centre allows the organisation to build, maintain, and manage customer relationships. This can be achieved by conducting transactions, providing information, responding to inquiries, and resolving issues and complaints quickly and more effectively than in-person interactions. This paper is based on pilot data collected from respondents similar to the original study population. The purpose was to investigate contact centre agents’ perceptions of technology adoption in promoting quality customer service. A quantitative research approach and a survey design were employed. A closed-ended questionnaire was used to collect primary data. The findings reveal that contact centre agents found technology to be both easy to use and valuable in providing effective customer service. Therefore, it is recommended that agents need to perceive technology acceptance as an essential element of providing excellent customer service.